Dynamic reciprocal relationships between traditional media reports, social media postings, and youth suicide in Taiwan between 2012 and 2021 - Ying-Yeh Chen; Feng Chen; Kevin Chien-Chang Wu; Tsung-Hsueh Lu; Ying-Chen Chi; Paul S.F. Yip (Elsevier, 2023)
Rising social media use over the past decade has been linked with increasing suicide rates among young people. Previous studies that assessed the impact of social media on suicide have typically focused on single social media platforms, such as Twitter, and assumed unidirectional associations, where social media posts leads to suicide. Our study focused on the past decade (2012-2021) which has witnessed a rapid increase of social media platforms and use. Poisson and negative binominal auto-regression models were employed to examine the dynamic reciprocity between social media, traditional media and youth suicides in Taiwan. Increased volume in suicide-related social media posts positively correlated with increased youth suicide rates (β = 2.53 × 10-5, 95% CI= (0.83 × 10-5, 4.24 × 10-5), P < 0.01), but increased rates of youth suicide was not related to an increase in suicide-related social media posts. Suicide-related posts on social media triggered reporting of suicide-related news on traditional media platforms (β = 3.35 × 10-2, 95% CI= (2.51 × 10-2, 4.19 × 10-2), P < 0.001), whilst traditional media reports of suicide led to increased suicide-related social media posts (β = 6.13 × 10-1, 95% CI = (4.58 × 10-1, 7.68 × 10-1); P < 0.001). However, suicide-related reports on traditional media platforms did not directly lead to an increase in youth suicide rates. Our findings highlight challenges for suicide prevention strategies in the 21st Century, in dealing with the increasing prominence of social media over traditional media. As social media is more difficult to regulate than traditional media, suicide prevention efforts must adapt to this new landscape by developing innovative strategies that address the unique risks and opportunities presented by social media.